MERCURY AND ARSENIC CONTAMINATION FROM SMALL SCALE GOLD MINING ACTIVITIES AT SELOGIRI AREA, CENTRAL JAVA, INDONESIA - Agung Harijoko; Tin May Htun; Rodhie Saputra; I Wayan Warmada; Lucas Donny Setijadji; Akira Imai; Koichiro Watanabe (Geological Engineering Department Universitas Gadjah Mada, 2015)
Small scale gold mines discussed here are located at Selogiri area, Central Java, Indonesia which was mined by local community mainly during gold rush in 1990s. This Selogiri gold deposit genetically is characterized by porphyry mineralization overprinted by epithermal system. The ore minerals assemblage consists of pyrite, sphalerite, chalcopyrite, galena, chalcocite and rare arsenopyrite. Chemical analysis of soil and stream sediment sampled over 1.5 km across at the Selogiri gold extraction site indicates that the site has been contaminated with mercury due to mining activities. The mercury concentrations in soil and stream sediments collected during dry season range from 0.01 to 481 ppm and 0.01 to 139 ppm, respectively, higher than background value of 0.05 ppm. In contrast, mercury concentration in stream sediments collected during rainy season from the same location as dry season sampling ranges from 0.01 to 13.42 ppm, and one sample has anomalous value of 331 ppm. This result show that rain water may disperse and decrease mercury concentration in stream sediments. In case of arsenic, although the ore contains rare arsenic minerals, arsenic concentration in bulk rock and ore is high ranging from 8 to 59 ppm, while the arsenic concentration in tailing is much higher ranging from 5.8 to 385 ppm. Chemical analyses on pyrite reveal that the pyrite grains contain arsenic and might be the source of arsenic in Selogiri mine site. However, analysis of dug-well water demonstrates that the mercury and arsenic content is still lower than the maximum allowable concentration. Keywords: Mercury, arsenic, contamination, Selogiri, gold mine